Electroacupuncture Regulates Inguinal White Adipose Tissue Browning by Promoting Sirtuin-1-Dependent PPARγ Deacetylation and Mitochondrial Biogenesis - Tang, Qianqian; Lu, Mengjiang; Xu, Bin; Wang, Yaling; Lu, Shengfeng; Yu, Zhi; Jing, Xinyue; Yuan, Jinhong (Frontiers in Endocrinology, 2021)
Background Previous studies had suggested that electroacupuncture (EA) can promote white adipose tissue (WAT) browning to counter obesity. But the mechanism was still not very clear. Aim In this study, we aim to study the effect of EA on promoting inguinal WAT (iWAT) browning and its possible mechanism. Method Three-week-old rats were randomly divided into a normal diet (ND) group and a high-fat diet (HFD) group. After 10 weeks, the HFD rats were grouped into HFD + EA group and HFD control group. Rats in the EA group were electro-acupunctured for 4 weeks on Tianshu (ST25) acupoint under gas anesthesia with isoflurane, while the rats in HFD group were under gas anesthesia only. Body weight and cumulative food intake were monitored, and H&E staining was performed to assess adipocyte area. The effect of EA on WAT was assessed by qPCR, immunoblotting, immunoprecipitation and Co-immunoprecipitation. Mitochondria were isolated from IWAT to observe the expression of mitochondrial transcription factor A (TFAM). Results The body weight, WAT/body weight ratio and cumulative food consumption obviously decreased (P < 0.05) in the EA group. The expressions of brown adipose tissue (BAT) markers were increased in the iWAT of EA rats. Nevertheless, the mRNA expressions of WAT genes were suppressed by 4-week EA treatment. Moreover, EA increased the protein expressions of SIRT-1, PPARγ, PGC-1α, UCP1 and PRDM16 which trigger the molecular conversion of iWAT browning. The decrease of PPARγ acetylation was also found in EA group, indicating EA could advance WAT-browning through SIRT-1 dependent PPARγ deacetylation pathway. Besides, we found that EA could activate AMPK to further regulate PGC-1α-TFAM-UCP1 pathway to induce mitochondrial biogenesis. Conclusion In conclusion, EA can remodel WAT to BAT through inducing SIRT-1 dependent PPARγ deacetylation, and regulating PGC-1α-TFAM-UCP1 pathway to induce mitochondrial biogenesis. This may be one of the mechanisms by which EA affects weight loss.